STAY OR LEAVE ? HOW DIGITAL UPSKILLING SHAPES LOYALTY AND REDUCES TURNOVER IN GENERATION Z EMPLOYEES - Dewi Tri Komalasari; Abdul Rahman Rahim (Integrative Perspectives of Social and Science Journal, 2026)
This study aims to analyze the role of digital upskilling in shaping loyalty and reducing turnover of generation z. Generation Z is known to be adaptive to technology and has high expectations for self-development, so companies need to respond through digital upskilling programs. This study used a descriptive qualitative approach with purposive sampling technique, involving 9 generation Z participants aged 22-28 years old who had participated in digital training. Data were collected through semi-structured interviews and analyzed thematically. The results showed that (1) digital upskilling is perceived as a form of corporate concern for employee development; (2) self-development opportunities increase loyalty through emotional attachment; and (3) the absence of training creates a feeling of stagnation that triggers turnover intentions. These findings reinforce Social Exchange Theory, where reciprocal relationships between companies and employees play a role in creating loyalty. The research recommends that companies make digital upskilling an ongoing program with flexible methods such as e-learning, and link it to career paths to retain generation Z talent.